How do athletes describe self-confidence? A qualitative study with young male and female volleyball players (Revista de Psicología, 2024)
The aim of this study was to describe perceptions about self-confidence in sport. Thirty players (50% female) of federated volleyball from a club in Mar del Plata, Argentina, between 14 and 18 years participated. An open-ended survey and the Grounded Theory analysis procedure were used. The categories emerged from the analysis to describe self-confidence were the belief in oneself for the achievement of goals; the social environment, mainly teammates and coaches; and positive self-talk and pre-execution routines, as the most used strategies to increase self-confidence. This work constitutes an input for the work of sports professionals in the search for the well-being and performance of young athletes.
Keywords: volleyball; self-confidence; performance; wellness